Effect of Manure Application on Root Morphology and Nitrogen (N) Uptake in the Roots of Rice (Oryza sativa L.) Variety M70D in Banyu Urip Village, West Lombok Regency - Lolita Endang Susilowati; Fatri Aisyah; Bambang Hari Kusumo; Isnaniar Rahmatul Azizah (JURNAL AGRIMENT, 2026)
Rice (Oryza sativa L.) is the main food crop in Indonesia, and increasing its productivity is very important. The productivity of rice plants is strongly influenced by root system development, which is affected by soil physical and chemical properties, especially under low-fertility dryland conditions. The agricultural land in Bentenu Hamlet, Banyu Urip Village, West Lombok Regency is classified as dryland with low soil fertility characterized by low organic carbon and total nitrogen contents as well as slightly acidic soil pH. This study aimed to determine the effect of cattle manure application on root morphology and nitrogen uptake of M70D rice plants. The research was conducted from June to September 2025 using a Randomized Block Design (RBD) with four treatments, namely P0 (0 ton ha⁻¹), P1 (2.5 ton ha⁻¹), P2 (5.0 ton ha⁻¹), and P3 (7.5 ton ha⁻¹) of cattle manure, with four replications. The observed parameters included root morphology and nitrogen uptake. Data were analyzed using ANOVA followed by the Honestly Significant Difference (HSD) test at the 5% level. The results showed that cattle manure application significantly affected root morphology and nitrogen uptake of rice plants. Treatment P3 produced the best results with the highest total root length (298.3 cm), root length density (1.23 cm cm⁻³), root volume (4.9 ml), root dry weight (0.80 g clump⁻¹), and nitrogen uptake (13.65 mg clump⁻¹). The application of cattle manure improved soil conditions and supported better root development and nitrogen absorption. Therefore, cattle manure at a dose of 7.5 ton ha⁻¹ has the potential to improve root morphology and nitrogen uptake of M70D rice grown on dryland.